Reinforcement of Aerospace Structural Elements Made of Layered Composite Materials. (2017) - Komarov, Valeriy A.; Pavlov, Alexander A.; Pavlova, Svetlana A.; Charkviani, Ramaz V.
Abstract: The paper investigates the possibility to apply some reinforcing techniques to enhance the interlaminar strength of layered composite materials. Experimental study of the efficiency of these methods was performed using curve-beam structural elements loaded by bending moment. Tests were carried out using a specially designed and produced testing tool with the maximum approximation to the requirements of ASTM D6415 standard. The obtained results provide a means to estimate the influence of strengthening techniques on the interlaminar strength of composite materials in a transverse direction. The article observes the following reinforcing methods: needling of carbon preform with aramid filament and introduction of special particles into the interlaminar voids. Experimental study of both needled and fiber-reinforced samples demonstrated that needling is more efficient (by 13-15%) for improving the interlaminar characteristics of layered composite material in transverse direction.